Zn doped ZIF67-derived porous carbon framework as efficient bifunctional electrocatalyst for water splitting. (26th July 2019) - Peng, Wencai; Zheng, Guoxin; Wang, Yuanbin; Cao, Shiyao; Ji, Zhen; Huan, Yahuan; Zou, Mingqiang; Yan, Xiaoqin
Abstract: The electrochemical splitting of water is considered to be an efficient and potential technique for producing clean hydrogen and oxygen. Although, there are lots of significant developments in composite of superior hydrogen evolution reaction (HER) or oxygen evolution reaction (OER) catalyst applied in water splitting currently, designing non-precious and low-cost bifunctional electrocatalysts with high performance is still an attractive challenging issue. In this article, we report a novel bifunctional electrocatalyst with cobalt-based nanoparticles (NPs) embedded in Zn-doped hierarchical porous three-dimension N-doped carbonization structure via an annealing process of metal organic frameworks (MOFs) connected by N-doped carbon nanotube (denoted as Co–Zn/PNC). This composite structure possesses the characteristics of more active sites, numerous mesopores and high conductivity. The resulting electrocatalyst (Co–Zn/PNC) can be used as both anode and cathode to roust the overall water splitting, getting a current density of 10 mA cm −2 at a cell voltage of 1.63 V in 1.0 M KOH electrolyte. Highlights: Co–Zn/PNC is prepared by Zn-doped ZIF-67 linked by N-doped CNT through pyrolysis. Bifunctional electrocatalyst Co–Zn/PNC exhibits excellent HER and OER performance. Zn doping can enhance the electrochemical performance of Co–Zn/PNC.